Quality assurance: Evaluation and comparison of methods for electron microscopic measurement of GBM width and the effect of in‐lab calibration in diagnostic renal pathology - Uner, Meral; Demirkol Canlı, Secil; Arend, Lois J. (Microscopy research and technique, 2022)
Replacing equipment and software can improve efficiency and allow updates to laboratory procedures, but has the potential to introduce changes in established values for a laboratory. Replacement of an electron microscope (EM), fitted with an updated digital camera, and use of new software for imaging and analysis prompted this QA study to ensure that new equipment, imaging, and measurement of the glomerular basement membrane (GBM) produced data consistent with the laboratory's established range of normal width. GBM measurements from 14 randomly selected human renal biopsies were compared using five different approaches. Original measurements of GBMs obtained on the laboratory's previous EM were compared to images collected on the new microscope with measurements performed using new software, as well as the original images and the new images measured using a separate software method as a control. The widths obtained by five approaches were compared to each other. While measurements showed minor variability between the approaches, significant difference in GBM width was noted in three of the paired comparisons. In some cases, these differences suggested slight diagnostic changes. Evaluation of new equipment, software, and techniques is important for a laboratory's quality assurance. While new equipment and/or procedures can introduce errors in test outcomes, we found that different EMs, cameras, and software made slight differences in our laboratory's values for kidney GBM width. However, a few cases showed enough difference in GBM width to suggest a change in diagnosis, illustrating the necessity of calibration adjustments in the setting of new equipment and software. Updating equipment and software has the potential to introduce errors in some aspects of established values for a given laboratory. To reduce diagnostic mistakes and misinterpretation, establishing an “in house” normal range for GBM thickness and re‐evaluating the range consequent to any replacement of equipment and software is recommended. Checking new software via a control method may provide a more precise calibration. Comparison of five glomerular basement membrane (GBM) measurement approaches using different EM camera and software combinations demonstrated a significant difference in GBM width that may have important consequences for pathologic diagnosis.